Study of effect of post heat treatment on mechanical properties of 3D printed high strength low carbon steel - Muhammad Hafiz Zailani (Nanyang Technological University, 2021)
Adoption of Additive Manufacturing (AM) has increased substantially over the past years which led to its process being adopted in many of the industries such as in aerospace, medical and automotive. Technologies in AM also have been rapidly evolving and now has over 7 broad categories of AM processes to cater to many materials and uses. However so, one such industry that lacks the exposure of AM in its processes is the Marine & Offshore industry. It is an industry where its applications surrounds harsh environments. The lack of research done for AM processes in this industry proving the reason for this. With Singapore being a major maritime hub, exploring the capabilities of AM in the Marine & Offshore industry is therefore key. The overall aim of this research proposal is to study the effect of heat treatment on the mechanical properties of EH36 steel. EH36 steel is a high strength low carbon steel that is being used as ship structural steel and in oil & gas transmission pipelines. Furthermore, the EH36 steel will be AM printed. In this project, it was found that through LENS a process in AM, the materials saw defects in them mainly as pits, pores and lack of fusion. Its presence will have effects on the material’s mechanical properties. Also, the different printing direction also bring about a difference in the material mechanical properties. However so, its build direction does not appear to influence much in the heat treatment process. Through heat treatment, it was shown how at different temperatures, the microstructures were affected.